In vitro antilithiatic potential of Kalanchoe pinnata, Emblica officinalis, Bambusa nutans, and Cynodon dactylon - Atul K Sohgaura; Papiya Bigoniya; B Shrivastava (Wolters Kluwer Medknow Publications, 2018)
Objective: The study aims at the exploration of calcium oxalate (CaOx) crystal growth inhibition potential of Cynodon dactylon, Emblica officinalis, Kalanchoe pinnata, and Bambusa nutans ethyl acetate fraction rich in polyphenol and flavonoid. Materials and Methods: Ethyl acetate fraction was separated from the hydromethanolic extract of C. dactylon, E. officinalis, K. pinnata, and B. nutans followed by quantitative analysis for total polyphenol and flavonoid content. Ethyl acetate fraction of all the plants were subjected to in vitro screening for the inhibition of CaOx crystals growth induced by sodium oxalate. Results: The results signify rich presence of polyphenols and flavonoids in K. pinnata and E. officinalis ethyl acetate fractions followed by C. dactylon and B. nutans. Ethyl acetate fractions of B. nutans shoot, E. officinalis fruit, and K. pinnata leaf have excellent in vitro CaOx crystal growth inhibition potential based on both the comparative concentration and the time level to achieve IC50. Conclusion: The study outcome substantiates potential in vitro CaOx crystal dissolution and crystal growth inhibition properties of E. officinalis, B. nutans, C. dactylon, and K. pinnata. Rich presence of caffeic acid, ferulic acid, and luteolin in ethyl acetate fraction of B. nutans leaf, and chebulinic acid, chebulagic acid, gallic acid, ellagic acid, and quercetin of E. officinalis may have produced prominent crystal aggregation inhibition response.